Contribution of Higher-Order Nonlinearity on Dust Acoustic Solitary Waves in Complex Plasma with a High-Energy Tail Ion Distribution - Younsi, Smain; Benzekka, Moufida; Amour, Nabil Arab; Rabia (Journal of Applied Nonlinear Dynamics, 2026)
The problem of dust acoustic dressed solitons is addressed in an unmagnetized collisionless dusty plasma with ions satisfying a κ-distribution. The approach based on the expanding of the Sagdeev potential up to the fourth-order has been generalized to the non-Maxwellian dusty plasma. This approach yields a second order inhomogeneous differential equation termed dressed soliton. The resulting dressed soliton is then expressed as a sum of the usual K-dV solution and the higher-order nonlinearity terms. The range of main parameters (κ and λ) where the higher order correction is valid is explored. In particular, the suprathermal parameter values required to the valid dressed solitons are shifted toward higher values as the velocity λ increases. Furthermore, our numerical investigations reveal that the main quantities of all localized structures are significantly modified by the suprathermal effects. Our results should help in providing a good fit between theoretical and experimental results.